Environmental challenges and social responses: A systematic qualitative review of vulnerable communities in Pakistan - Zubair, Asim (Abdul Media Literasi, 2026)
Pakistan is exceptionally vulnerable to climate-induced hazards such as floods, droughts, and water scarcity, which disproportionately affect its most vulnerable communities. This systematic qualitative review synthesizes evidence to examine the interplay between these environmental challenges and the social responses of at-risk populations. The objective was to understand how socioeconomic factors shape vulnerability and to identify the coping and adaptive strategies communities employ. Following a PRISMA-style screening approach, a comprehensive search of academic databases (Scopus, Web of Science, Google Scholar) and institutional reports yielded 41 studies for narrative synthesis, guided by Vulnerability Theory. Key findings reveal that recurrent floods in Punjab and Sindh, and prolonged droughts in Balochistan, exacerbate economic losses, displacement, and health risks. In response, communities use short-term coping mechanisms, such as temporary migration and borrowing, alongside long-term adaptive measures, such as crop diversification, water management, and local disaster committees. The synthesis of Focus Group Discussions and Key Informant Interviews highlights that adaptive capacity is critically shaped by income, education, gender, social networks, and institutional support, with women and youth facing distinct vulnerabilities. The findings underscore the need for integrated, community-centered policies that combine hazard mitigation with socioeconomic support and institutional strengthening. This review contributes to evidence-based policymaking for sustainable disaster management and climate adaptation in Pakistan.